2013
DOI: 10.1089/scd.2012.0498
|View full text |Cite
|
Sign up to set email alerts
|

MePR: A Novel Human Mesenchymal Progenitor Model with Characteristics of Pluripotency

Abstract: Human embryo stem cells or adult tissues are excellent models for discovery and characterization of differentiation processes. The aims of regenerative medicine are to define the molecular and physiological mechanisms that govern stem cells and differentiation. Human mesenchymal stem cells (hMSCs) are multipotent adult stem cells that are able to differentiate into a variety of cell types under controlled conditions both in vivo and in vitro, and they have the remarkable ability of self-renewal. hMSCs derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 106 publications
1
34
0
Order By: Relevance
“…1A). The acquisition of the typical neural phenotype, previously described by Miceli et al [24], was further confirmed by the increase, upon MePR-2B differentiation, of intracellular calcium, a typical hallmark of neuronal differentiation (Fig. 1B).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…1A). The acquisition of the typical neural phenotype, previously described by Miceli et al [24], was further confirmed by the increase, upon MePR-2B differentiation, of intracellular calcium, a typical hallmark of neuronal differentiation (Fig. 1B).…”
Section: Resultssupporting
confidence: 83%
“…MePR-2B cells can be cultivated as undifferentiated cells but, upon appropriate stimuli, can undergo myogenic, adipogenic, osteogenic, chondrogenic and neuro-glial differentiation [24]. In this work, a targeted secretome characterization was performed on undifferentiated cells (MePR-2B) and after the acquisition of morphological and physiological features typical of neuro-glial differentiation (MePR-2B/D) [24]. As expected, a typical spindle-shaped, fibroblastic-like morphology was observed for undifferentiated MePR-2B cells while, following differentiation, a neurallike morphology was acquired as attested by the appearance of a translucid shape with long extensions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human colon cancer HCT-116 (ATCC, VA, USA) and HCT-116 p53 ¡/¡ (DSMZ, Braunschweig, Germany) cells were propagated in McCoy's 5A medium (Euroclone, Milan, Italy) with 10% fetal bovine serum (FBS) (Euroclone), 2 mM L-glutamine (Euroclone) and antibiotics (100 U/ml penicillin, 100 lg/ml streptomycin) (Euroclone). 38 Human leukemic monocyte lymphoma U937 cells 39 (ATCC) and mesenchymal progenitor (MePR2B) cells 40 were propagated in RPMI 1640 medium containing 4.5 g/L glucose (Euroclone) supplemented with 10% FBS (Euroclone), 100 U/mL penicillin-streptomycin (Euroclone) and 2 mM L-glutamine (Euroclone). Cells were stimulated with drugs for 12 h, 24 h, 48 h, and 24 h C 24 h (drugs were added again 24 h post-24 h stimulation).…”
Section: Cell Linesmentioning
confidence: 99%
“…Cells were first grown for 24 h and then infected with the rLV.H1.sh2Sirt1.EF1.GFP Lentivirus, with a 2.5 MOI, overnight as described by Miceli et al [27]. …”
Section: Methodsmentioning
confidence: 99%
“…Cell cycle distribution was assessed with a FACScalibur flow cytometer (Becton Dickinson, San Jose, CA, USA), and 10.000 cells were analyzed by ModFit version 3 Technology (Verity Software House, Topsham, ME, USA) and Cell Quest (Becton Dickinson, San Jose, CA, USA) [27]. …”
Section: Methodsmentioning
confidence: 99%